Cyber-Bullying in Sophie Mckenzie's "Sweetfreak" - Naufal, Maulana Mochammad (SIGEH ELT : Journal of Literature and Linguistics, 2024)
This research is about the cyber-bullying in Sophie Mckenzie’s SweetFreak. This research’s objectives are to describe the extrinsic element that are the causes, types and effects of cyber-bullying in the novel. This research used psychological approach in its method and the descriptive qualitative method for its research design. Through the use of the Lifestyle-Routine Activity Theory by Candace et al. (2023) a theory to determine the likelihood of victimization, the researcher found that the cyber-bullying in this novel happened because of three factors: motivated offender, target suitability, absence of guardianship. The motivated offender factor happened because the culprit of the cyber-bullying was driven to do the cyber-bullying, target suitability factor happened because the victim of the cyber-bullying had done something prior that made her suitable to be targeted by the perpetrator, the absence of guardianship happened because no real elders in the novel ever tried to protect or supervised the victim. Then in terms of types of cyber-bullying, the researcher found that there are five types of cyber-bullying that are used in the novel. The types of cyber-bullying are: online harassment, flaming, denigration, photograph & video, fraping. As for the effects, the researcher found there are three kinds of effect from the cyber-bullying, that are displayed by the main character in the novel. They are: academic effect, which disrupts the main character’s school life, the social effect that ruined the main character’s interaction with her peers, and finally the emotional effect that disturbed the psyche of the main character.